(untitled) (White Plains, NY, 2011)
Real Reading provides students with a meaningful and authentic reading experience. Compelling readings in a variety of genres have been carefully written or adapted from authentic sources and feature a principled approach to vocabulary development.
Keywords: Đọc hiểu,English language,Reading comprehension,Vocabulary